Sustainable Reimbursements: Towards a Unified Framework for Pricing Drugs with Significant Uncertainties - Sylvain Chassang; Valentina Mantua; Erik Snowberg; Entela Xoxi; Luca Pani (Center for Economic Studies and ifo Institute (CESifo), 2018)
Recent political events have thrust the bulk negotiation of drug prices by Medicare and Medicaid back into the spotlight. Yet, even if politically feasible, there is no clear framework for negotiating prices of new drugs with uncertain target populations—for example, due to imprecise estimates or off-label use—or uncertain clinical effects—for example, due to heterogeneous patient response. We create such a framework using two-price programs developed in the economics of procurement literature. This framework delivers new payment strategies, and unifying them with theoretical advances in pharmaceutical reimbursement like capitation and value-based pricing. Two-price programs substantially reduce uncertainty for both payers and pharmaceutical companies, while still creating financial incentives for those companies that innovate and create value for patients.
Keywords: H51; I11; I18; 330